2002
DOI: 10.1021/es015796w
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrene Sorption by Aliphatic-Rich Natural Organic Matter

Abstract: Contaminant sorption, an important process that may limit bioavailability, hinder remediation, encourage environmental persistence, and control mobility in the environment, has been the focus of numerous studies. Despite these efforts, the fundamental understanding of sorptive processes in soil and sedimentary environments has not been resolved. For instance, many have suggested that contaminants, such as polycyclic aromatic hydrocarbons (PAHs), solely interact with aromatic domains of organic matter. Until no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
242
3
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(272 citation statements)
references
References 55 publications
21
242
3
3
Order By: Relevance
“…The 13 C NMR spectral results obtained in the present study suggest that mycorrhizal colonization changes root surface and composition characteristics and this has important implications for the uptake of phenanthrene by plant roots because the association between hydrophobic pollutants and root components determines the surface sorption and transfer of hydrophobic pollutants into plant tissues. Numerous investigations have indicated that sorption of hydrophobic pollutants is regulated mainly by aromatic domains of organic matter (Chin et al, 1997;Chiou et al, 1998) although some other studies suggest a negligible contribution of aliphatic C (Salloum et al, 2002;Lin et al, 2007). Mycorrhizal roots had higher aromatic C and therefore their affinity for phenanthrene was higher than that of non-mycorrhizal roots with lower aromatic C, which is consistent with the observation of higher adsorption and lower desorption of phenanthrene by mycorrhizal roots.…”
Section: C Nmr Spectral Analysissupporting
confidence: 78%
“…The 13 C NMR spectral results obtained in the present study suggest that mycorrhizal colonization changes root surface and composition characteristics and this has important implications for the uptake of phenanthrene by plant roots because the association between hydrophobic pollutants and root components determines the surface sorption and transfer of hydrophobic pollutants into plant tissues. Numerous investigations have indicated that sorption of hydrophobic pollutants is regulated mainly by aromatic domains of organic matter (Chin et al, 1997;Chiou et al, 1998) although some other studies suggest a negligible contribution of aliphatic C (Salloum et al, 2002;Lin et al, 2007). Mycorrhizal roots had higher aromatic C and therefore their affinity for phenanthrene was higher than that of non-mycorrhizal roots with lower aromatic C, which is consistent with the observation of higher adsorption and lower desorption of phenanthrene by mycorrhizal roots.…”
Section: C Nmr Spectral Analysissupporting
confidence: 78%
“…Lipids can not only serve as a diagnostic index of soil biological activity, but also act as the dominant sorption domains in forest and agricultural soils (32,33). Linear sorption was found for phenanthene on lipid-modified clay (34).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that sorption capacity of HOCs was positively related to aromaticity of humic and fulvic acids (Perminova et al, 1999), and was negatively correlated with certain polarity indices of NOM derived from elemental ratios (Grathwohl, 1990;Xing et al, 1994). However, other investigators (Chefetz et al, 2000;Salloum et al, 2002) revealed that aliphatic carbon of NOM could significantly contribute to sorption of HOCs. From the above investigations, it is known that a few investigations have examined relationships of composition and structure of algae with the biosorption of HOCs.…”
Section: Introductionmentioning
confidence: 95%
“…The bulk market algal species, cultured algal species, and field-collected plankton samples have H/C ratios of 1.76-1.81, 2.26-2.28 and 1.88-2.13, respectively (Table 1), exhibiting a high aliphatic nature. Zelibor et al (1988) and Salloum et al (2002) reported that the H/C ratios varied slightly, ranging from 1.6 for Dunaliella tertiolecta and Scenedesmlus obliquus to 1.7 for Chlorella pyrenosidosa and Botnyococcus brautnii. The H/C ratio of C. pyrenosidosa is 1.7, lower than 2.28 for Chlorella in this study.…”
Section: Composition and Elemental Ratios Of Bulk Algae And Isolated mentioning
confidence: 99%